Factors influencing computer attitude of library staff of the De La Salle University library - Ramos, Marian S. (2000)
As computer literacy and computer use become more and more important in library systems, the attitude of library staff towards computers play an important role in the successful implementation of computerization. The study examined the attitudes of library staff of the De La Salle University Library towards computers and explored the effects of their age, sex, educational attainment, computer experience, position classification and library department on their attitudes toward computers.